An electron miniaccelerator on the basis of Tesla transformer for nondestructive testing of charged particle beams - Akimov, V.E.; Bulatov, A.V.; Logatchev, P.V.; Kazarezov, I.V.; Korepanov, A.A.; Maljutin, D.A.; Starostenko, A.A. (Вопросы атомной науки и техники, 2006)
An electron miniaccelerator on the basis of Tesla-transformer for nondestructive testing of charged particle beams with operating voltage 120…200 kV, half-wave duration 4 mks and diagnostic beam current within few mA is described. The primary circuit is switched by IGBT. The gun control and filament circuit power supply (impregnated cathode with 1.2 mm diameter) are realized through high frequency isolated transformer. The accelerating tube is made of sectional welded metal ceramics insulator (ceramics 22HS with diameter 95/85 mm).The accelerator test results are presented.